The feral pig of the Pantanal - Pedrosa, Felipe; Keuroghlian, Alexine; Oliveira-Santos, Luiz Gustavo Rodrigues; Desbiez, Arnaud Léonard Jean (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The feral pig of the Pantanal is an iconic species. Introduced into the wetlands by the region’s first settlers, it became feral from the end of the 19th century. Since then, it has gradually expanded its distribution and abundance, currently occupying practically the entire Pantanal. Throughout the more than 120 years of Pantanal occupation, the porco-monteiro has demonstrated several ecological and socio-environmental roles and impacts. On the one hand, they function as prey for the jaguar, are frugivores and seed dispersers, relieve the hunting pressure on native species, and are an important source of animal protein to the Pantanal people. On the other hand, the feral pig competes with the native fauna for food resources, are reservoirs of diseases of economic and human importance, destroy subsistence plantations and prey on calves and lambs from farms.
Keywords: Hunting; Invasive species; Wildlife management; Sus scrofa